Prevention of advanced cancer by vitamin D3 supplementation: interaction by Body Mass Index revisited - Brenner, Hermann; Kuznia, Sabine; Laetsch, Dana Clarissa; Niedermaier, Tobias; Schöttker, Ben (Nutrients, 2021)
Meta-analyses of randomized controlled trials (RCTs) have demonstrated a protective effect of vitamin D3 (cholecalciferol) supplementation against cancer mortality. In the VITAL study, a RCT including 25,871 men ≥ 50 years and women ≥ 55 years, protective effects of vitamin D3 supplementation (2000 IU/day over a median of 5.3 years) with respect to incidence of any cancer and of advanced cancer (metastatic cancer or cancer death) were seen for normal-weight participants but not for overweight or obese participants. We aimed to explore potential reasons for this apparent variation of vitamin D effects by body mass index. We conducted complementary analyses of published data from the VITAL study on the association of body weight with cancer outcomes, stratified by vitamin D3 supplementation. Significantly increased risks of any cancer and of advanced cancer were seen among normal-weight participants compared to obese participants in the control group (relative risk (RR), 1.27; 95% confidence interval (CI), 1.07-1.52, and RR, 1.44; 95% CI, 1.04-1.97, respectively). No such patterns were seen in the intervention group. Among those with incident cancer, vitamin D3 supplementation was associated with a significantly reduced risk of advanced cancer (RR, 0.86; 95% CI, 0.74-0.99). The observed patterns point to pre-diagnostic weight loss of cancer patients and preventive effects of vitamin D3 supplementation from cancer progression as plausible explanations for the body mass index (BMI)—intervention interactions. Further research, including RCTs more comprehensively exploring the potential of adjuvant vitamin D therapy for cancer patients, should be pursued with priority.